The Comparison of Youth Self-Concepts Assessed from Parenting Style - Setiana, Setiana; Darmayanti, Darmayanti (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2020)
This article contains an analytical description of the self-concept of adolescents in terms of parenting styles. The research method used in this research is conceptual and empirical studies in the fields of social psychology, parenting and sociology about self-concepts developed by parenting styles. The findings of this article reveal a comparison of adolescent self-concepts based on parenting styles so that it can be used as a basis for understanding self-concept, where authoritative parenting styles can develop positive adolescent self-concepts.